2009
DOI: 10.1002/jso.21362
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of immunohistochemically detected lymph node micrometastases in pT0N0 esophageal squamous cell carcinoma

Abstract: LNMs are uncommon in pathological complete responders but hold prognostic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…There is a strong body of evidence suggesting that immunohistochemically detected micrometastatic deposits in oesophageal cancer are associated with reduced survival and increased risk of disease recurrence [55][56][57][58][59][60][61][62][63][64][65]. Several studies have identified micrometastatic spread to be an independent prognostic indicator in oesophageal adenocarcinoma [35,39,41,43,66] and it has been postulated that these micrometastatic deposits may help to explain why up to 50% of histologically nodenegative oesophageal cancer patients develop recurrence, despite a curative resection of the primary tumour [67,68].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…There is a strong body of evidence suggesting that immunohistochemically detected micrometastatic deposits in oesophageal cancer are associated with reduced survival and increased risk of disease recurrence [55][56][57][58][59][60][61][62][63][64][65]. Several studies have identified micrometastatic spread to be an independent prognostic indicator in oesophageal adenocarcinoma [35,39,41,43,66] and it has been postulated that these micrometastatic deposits may help to explain why up to 50% of histologically nodenegative oesophageal cancer patients develop recurrence, despite a curative resection of the primary tumour [67,68].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…On the other hand, it has been reported that micrometastases, including an individual cancer cell and clustered tumor cells, could be a prognostic factor in EC . Cytokeratin (CK) immunohistochemistry (IHC) using antibody AE1/AE3 is a common method to detect micrometastases in lymph nodes . However, the clinical significance of the number of occult MLNs remains unclear because of the complexity of the procedure to detect occult MLNs.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Cytokeratin (CK) immunohistochemistry (IHC) using antibody AE1/AE3 is a common method to detect micrometastases in lymph nodes. [5][6][7] However, the clinical significance of the number of occult MLNs remains unclear because of the complexity of the procedure to detect occult MLNs. There is also a report that single cells cannot proliferate in lymph nodes because they have already been killed by local and general immunocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the inability to identify residual tumor cells in surgical specimens should by no means be considered as a synonymous of cure because up to one third of such patients will ultimately develop disease recurrences . To date, there have been only a few studies that have attempted to identify the main risk factors for disease recurrence …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] To date, there have been only a few studies that have attempted to identify the main risk factors for disease recurrence. 9,10 The diagnosis of pCR is established by pathological examination of the resected specimens using routine hematoxylin and eosin (H&E) staining. However, consensus criteria for guiding the pathological examination in patients with esophageal cancer who receive nCRT have not yet been established.…”
Section: Introductionmentioning
confidence: 99%